2018
DOI: 10.1002/nop2.181
|View full text |Cite
|
Sign up to set email alerts
|

Implementing and feasibility testing depression screening using the electronic medical record for patients with type 2 diabetes admitted to the hospital

Abstract: AimIs it feasible to implement a programme to screen for depression in patients admitted to the hospital for diabetes complications and use the electronic medical record to notify providers of their patient's depression score and give suggestions for medication and counselling?DesignA feasibility study was conducted with patients hospitalized with diabetes and depression in the Durham Veterans Affairs Medical Center, Durham, North Carolina, United States.MethodsPatients with type 2 diabetes were screened for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Due to numerous analyses confirming the presence of depressive symptoms among people suffering from type 2 diabetes, the conclusion that there is a need for screening research in this direction can be drawn. The team led by Joseph et al [27] confirmed such a possibility and at the same time proved that it would allow for the provision of quick and professional help to patients. According to Joseph et al, each member of the interdisciplinary team can carry out screening research.…”
Section: Discussionmentioning
confidence: 94%
“…Due to numerous analyses confirming the presence of depressive symptoms among people suffering from type 2 diabetes, the conclusion that there is a need for screening research in this direction can be drawn. The team led by Joseph et al [27] confirmed such a possibility and at the same time proved that it would allow for the provision of quick and professional help to patients. According to Joseph et al, each member of the interdisciplinary team can carry out screening research.…”
Section: Discussionmentioning
confidence: 94%